The novel non‐steroidal MR antagonist finerenone improves metabolic parameters in high‐fat diet‐fed mice and activates brown adipose tissue via AMPK‐ATGL pathway. Issue 9 (30th July 2020) - Marzolla, Vincenzo; Feraco, Alessandra; Gorini, Stefania; Mammi, Caterina; Marrese, Carmen; Mularoni, Valentina; Boitani, Carla; Lombès, Marc; Kolkhof, Peter; Ciriolo, Maria Rosa; Armani, Andrea; Caprio, Massimiliano
Abstract: Mineralocorticoid receptor antagonists (MRAs) are recommended for the treatment of heart failure and hypertension, mainly due to their natriuretic and anti‐fibrotic mode of action. Rodent studies have shown that MRAs can prevent adverse metabolic consequences of obesity but an elucidation of underlying molecular mechanisms is missing. Here, we investigated metabolic effects of the novel non‐steroidal MRA finerenone (FIN) in a mouse model of high‐fat diet (HFD)‐induced obesity and the signaling pathways activated by MR antagonism at level of interscapular brown adipose tissue (iBAT). C57BL/6J male mice were fed a normal diet or a HFD (with60%   kcal from fat) containing or not FIN for 3 months. Metabolic parameters, adipose tissue morphology, gene and protein expression analysis were assessed. We also used brown adipocyte cultures (T37i cells) to investigate the effects of FIN‐mediated MR antagonism upon lipid and mitochondrial metabolism. HFD + FIN‐treated mice showed improved glucose tolerance together with increased multilocularity and higher expression of thermogenic markers at the level of iBAT, without differences in white adipose depots, suggesting an iBAT‐specific effect of FIN. Mechanistically, FIN increased activation of AMP‐activated protein kinase which, in turn, stimulated adipose triglyceride lipase activation, with subsequent increased expression of uncoupling protein‐1 in brown adipocytes.